Analog Speed-Control of DC-Motor Using Proportional and Proportional-Integral Controllers - Halboot Mohussen, Deia (Journal of Engineering and Sustainable Development, 2011)
A systematic development of the analysis, design, and testing by simulation of a closed-loop speed control of separately excited dc motor drive system is described in this paper. The motor controlled armature voltage is supplied from a three-phase fully controlled bridge converter. Closed-loop control is analyzed by using transfer function techniques and the necessity of an inner current control loop is demonstrated. Designs of both a proportional and proportional-integral controllers are outlined by using transfer function technique. A soft starting concept is used to reduce the value of starting current. The feed forward loop is used to reduce the effect of load torque disturbances. The speed and current responses are also presented for load and no-load cases.